Manufacturing and characterisation of photoresponsive composites for defence applications - Christogianni, Paraskevi (Cranfield University, 2017)
The development of composites with improved mechanical and impact resistance properties has attracted considerable attention within the defence and aerospace industries. These composites are finding applications in vehicle or aircraft structures which are frequently exposed to impact from bird strikes, hailstorm, dropped tools and runway debris. In addition, exposure to extreme conditions such as high levels of UV light exposure or extreme temperatures increases the brittleness of the polymer matrix, ultimately leading either to the loss of mechanical properties such as compression strength or even to the catastrophic structural failure of the composites. The aim of this PhD project was to develop toughened and self-healing composites in which delamination and crack growth can be managed to an acceptable level. This was attempted using a new epoxy-based resin modified with photoresponsive azobenzene. Mechanical properties of the composites, toughened by azobenzene, were improved as a result of the photo-induced changes in the azobenzene structures. Initial works were to identify, synthesise and characterise appropriate photoresponsive resins that were thought to offer composites with enhanced properties. The synthesis of azobenzene acrylic- and epoxy-based polymers were accomplished using conventional wet chemistry. Their properties were triggered by different stimuli and characterised using 1H NMR, UV/Vis and FTIR spectroscopy, DSC, GPC, rheology, and nanoindentation. The azobenzene/acrylic-based copolymer films showed a significant photomechanical behaviour. Nanoindentation analysis demonstrated a maximum increase in stiffness of 19% with an optimum azobenzene loading of 30 mol%. Such an enhancement in stiffness was attributed to the photoinduced reorganisation of the polymer chains by geometrical isomerisation (trans to cis isomers) of the azobenzene chromophores. Analysis of the thin films by optical microscopy demonstrated a healing effect of the indented region under UV irradiation suggesting that this class of polymers can be used as self-healing materials. Ultrasound was also found to trigger cis  trans isomerisation in the solid state at a much slower rate (120-150 min) than by visible light (30-60 s). Azobenzene-modified epoxy resins were synthesised by optimising an existing synthetic route and their responses to light and curing behaviour with a common amine hardener (a curing agent for epoxy resin, used to initiate curing/hardening) were assessed. The resulting kinetic reactions were investigated using isothermal (95°C) and dynamic heating scans (30-180°C) in a DSC and by simultaneously monitoring the spectral information using a NIR-FTIR spectrometer. The modified epoxy azobenzene resin proved to be reactive enough to form a network that can withstand temperatures of up to 200°C. The azobenzene-epoxy resins exhibited high dimensional stability, stiffness enhancement and healing behaviour when they were exposed to UV light. Gas pycnometer studies demonstrated constant volume and density values of the resins before and after UV irradiation. Optical and atomic force microscopes were used to assess and quantify the healing effect of damaged azobenzene-based polymer films. An intrinsic healing (73% of the total damaged area) was caused by the UV-induced molecular mobility of azobenzene in a 3D crosslinked network. The influence of UV light and the effect of azobenzene loading on the epoxy-based polymeric matrices were also evaluated after fracture mechanics analysis and it was found that an 11% increase in fracture toughness was observed with 10 mol% azobenzene (without exposure to UV light). On the contrary UV light increased the brittleness of the matrix with higher azobenzene loading. The azobenzene-modified epoxy resin was used to produce glass fibre-reinforced composites. Their photo-induced properties were investigated by compression, impact and post-impact compression testing. The composites exhibited an increase (3-16%) in compressive strength after exposure to UV light due to the trans  cis isomerisation. Moreover, it was demonstrated that the introduction of a small fraction of azobenzene (10 mol%) into the composites enhanced their impact resistance by 10% when subjected to high velocity impacts (190 m/s). The absorbed energy of the azobenzene composites which had been previously exposed to UV light was also increasing linearly with the azobenzene loading.